Laser processing: solutions for industry: Comprehensive preview to Laser Symposium and the 4th International Symposium for Additive Manufacturing (ISAM), 2021. Issue 6 (3rd November 2021) - Leyens, Christoph; Standfuß, Jens; Wetzig, Andreas; Brückner, Frank; Barbosa, Maria; Hauptmann, Jan; Lopez, Elena; Seifert, Marko; Dittrich, Dirk; Herwig, Patrick; Hillig, Holger; Stepien, Lukas; et al.
Abstract: Over at least the last four decades, laser‐based processes have matured from niche applications to widely accepted tools in industrial processing chains. Starting with CO2 lasers, the development of new laser sources such as fiber and disk lasers, either continuous‐wave or pulsed, have boosted the use of lasers for cutting, joining, surface modification and heat treatment, coating and – more recently – additive manufacturing, to name just a few applications.